BMH as body language : a lexical and iconographical study of the word BMH when not a reference to cultic phenomena in biblical and post-biblical Hebrew - Barrick, W. Boyd, 1946- (Library of Hebrew Bible/Old Testament studies, 2008)
It is customarily assumed that the Hebrew word BMH denotes a "high place," first a topographical elevation and derivatively a cult place elevated either by location or construction.€This book offers a fresh, systematic, and comprehensive examination of the word in those biblical and post-biblical passages where it supposedly carries its primary topographical sense.€Although the word is used in this way in only a handful of its attestations, they are sufficiently numerous and contextually diverse to yield sound systematic, rather than ad hoc, conclusions as to its semantic content. & nb